The impact of environmental conditions on lifestyle quality in industrial and non-industrial region in the Czech Republic - Riedlova, Petra; Tomaskova, Hana; Slachtova, Hana; Babjakova, Jana; Jirik, Vitezslav (Frontiers in Public Health, 2025)
BackgroundLong-term exposure to air pollution is associated with a higher incidence of various non-infectious diseases. However, not only air pollution, but also other risk factors, such as lifestyle, can play a role in the occurrence of these diseases or premature deaths from them. The study aimed to compare the lifestyle of residents of two differently air polluted regions and to determine how lifestyle is affected by socioeconomic variables.MethodsIn the framework of the project Healthy Aging in Industrial Environments, two cohorts of persons from an industrial area and a control area were established. The cohorts consisted of individuals aged 35 to 65 years. Lifestyle factors included diet, BMI, alcohol and cigarette consumption, duration of sleep, physical activity, and time spent doing hobbies. Influencing factors included region, sex, age, education, family status, and economic situation. Fully adjusted binary and ordinal logistic regression models were used for evaluation, and the output was the odds ratio (OR) with 95% confidence intervals (CI).ResultsThe effect of more air polluted industrial region was related to higher BMI (OR = 1.23; 95% CI: 1.08–1.4) and physical activity (OR = 1.31; 95% CI: 1.13–1.51) and surprisingly to lower smoking level (OR = 0.84; 95% CI: 0.74–0.99).ConclusionThe results of our study are useful in targeting public health strategies and intervention programs to specific populations, and the results will be share with public awareness groups that focus on prevention and the physiological aspects of physical activity.